Ultrafast and durable lithium ion storage enabled by intertwined carbon nanofiber/Ti2Nb10O29 core-shell arrays. (1st February 2020) - Tang, Yulin; Deng, Shengjue; Shi, Shaohua; Wu, Lihong; Wang, Guizhen; Pan, Guoxiang; Lin, Shiwei; Xia, Xinhui
Abstract: Ti2 Nb10 O29 (TNO) has been extensively regarded as a promising material for lithium-ion batteries (LIBs) in view of its large theoretical capacity and high structural stability. Nevertheless, accomplishing ultrafast and durable lithium storage meets a challenge of designing TNO-based nanostructure with improved electronic conductivity and favorable kinetics. Herein, the binder-free hierarchical carbon nanofibers@TNO arrays grown on carbon cloth (CNFs@TNO/CC) are prepared by a facile electrophoretic deposition & solvothermal method. The intertwined CNF arrays as both an excellent bridge and a strong support can endow TNO with high conductivity, good mechanical stability and large surface area. TNO particles attached to CNF surface are also limited at a narrow size of distribution (20–50 nm), which decreases the Li-ion transport pathways and improves the Li-ion diffusion coefficients. Thus, the remarkably high Li-ion diffusion coefficients are achieved for the present CNFs@TNO/CC. CNFs@TNO/CC arrays manifest an excellent capacity of 308 mA h g −1 at 1 C with a high initial Coulombic efficiency of 91%. A capacity retention of 192.6 mA h g −1 (91% initial capacity) is achieved after 1000 cycles at a rate of 10 C. Our work illustrates that the CNFs@TNO/CC as a promising anode material, exhibits great potential application for ultrafast LIBs. Graphical abstract: Image 1 Highlights: Hierarchical carbon nanofibers@Ti2 Nb10 O29 arrays grown on carbon cloth (CNFs@TNO/CC) are prepared. Carbon nanofiber arrays endow Ti2 Nb10 O29 with tridimensional conductivity and fast Li-ion transfer efficiency. CNFs@TNO/CC shows remarkably high Li-ion diffusion coefficients. CNFs@TNO/CC exhibits a high reversible capacity of 308 mA h g −1 at 1 C. A capacity retention of 78% at 10 C are achieved after 1000 cycles.